Biofilm-Based Nosocomial Infections - Gianfranco Donelli (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2015)
Microbial biofilms have been implicated in a large number of acute and chronic infections, as well as in the failure of antibiotic treatment, particularly in hospitalized patients. In fact, the well-known persistence in the nosocomial environment of multidrug resistant microorganisms is believed to be highly promoted by the ability of the great majority of the involved bacterial and fungal species to adhere on living or abiotic surfaces, and to grow in sessile mode, to form single- or multi-species biofilms. In these communities, microbes grow encased in a hydrated matrix of extracellular polymeric substances produced by themselves and are well protected from the host immune response and the attack of antimicrobial molecules. Thus, the establishment of microbial biofilm communities on the mucosal and soft tissues of hospitalized patients, as well as on the surfaces of indwelling devices and medical instruments, is expected to have a great influence on the success of the antibiotic therapies against most of the bugs involved in nosocomial infections, being biofilm-growing bacteria and fungi much less susceptible to antibiotics.